Accumulation, Timing, and Duration of Early Childhood Adversity and Behavior Problems at Age 9. Issue 1 (2nd January 2020) - Schroeder, Allison; Slopen, Natalie; Mittal, Mona
Abstract : We utilized a life course framework to examine associations between the accumulation, timing, and duration of adverse childhood experiences (ACEs) across early childhood (ages 1–5 years) and internalizing and externalizing behavior problems at age 9. The sample included 1, 789 children from the Fragile Families and Child Wellbeing Study, a birth cohort study of children born between 1998 and 2000. Primary caregivers reported on seven ACEs at child ages 1, 3, 5, and 9. We created 2 summary measures of early childhood ACEs to capture (a) accumulation and (b) timing and duration. We derived indicators of caregiver-reported internalizing and externalizing problems at ages 5 and 9. Logistic regression was used to estimate associations between early childhood ACEs and behavior problems at age 9, sequentially adjusting for sociodemographic covariates, age 9 ACEs, and age 5 behavior problems. In fully adjusted models, children exposed to 6 or more ACEs in early childhood faced 3 times the odds of age 9 behavior problems, compared to children exposed to 0–1 ACE. Intermittent adversity was associated with the greatest increase in odds of age 9 behavior problems, relative to other early childhood timing/duration categories. Categories of high early and high late adversity were also associated with age 9 behavior problems. Chronic adversity was not associated with age 9 behaviors in final models that adjusted for age 5 problems. These results demonstrate the importance of a developmental perspective for understanding the role of childhood adversity in the etiology of child psychopathology.